Demonstration polymerase chain reaction (PCR) videotape series - Morrey, John D; Lowry, William (Utah : Taped Technologies, 1991)
Demontrate polymerase chain reaction which are excerpts from these videos : polymerase chain reaction (PCR) and detection, avoiding false positives in PCR, sample preparation for PCR, DNA sequencing using PCR.
Keywords: DNA polymerases; Polymerase chain reaction